As interações entre o setor saúde e a saúde mental a partir das estatísticas de ciência e tecnologia - Catari Vilela Chaves (2005)
The aim of this thesis is to place the mental health theme within the discussion about the innovation health system.Firstly, the health sector was compared to the other sectors of economic activity from a theoretical point of view. As the differences among them proved to be substantial, studies on the health sector started to be carried out. The focus of the present thesis was to evaluate if there is something to differentiate mental health from general health. The bibliography used indicates that there are strong similarities, as the especifities of mental health determine a set of connections within the health innovation system, thus justifying a joint investigation into mental health. Therefore, the concept of a system of health innovation was used to organize the discussion.Once mental health is placed within the health innovation system, a number of illnesses, under the common denominator of mental illnesses, can be investigated aiming at expanding the understanding of how they can be linked to the health sector system. Statiscally, through the crisp sets and fuzzy sets, the evaluation based on data from general health and mental health in particular, indicates that competence in the mental health area presupposes a presence in terms of quantity and emphasis on general health. But to have this link, it was necessary, first of all, to know the particularities of health in general vis-à-vis the national innovation system (NSI).A preliminary typology of countries made by means of the methodology of hierarchical clusters has identified a threshold in scientific production, both for the NSI and the health NSI. The difference between them lies in the scientific-technological discontinuity in the health sector. This means that in order to go over the threshold of scientific production and get into more advanced stages of development, the developing countries need to expand significantly their scientific-technological infra-structure in health, as concerns the NSI.It is known that the relationship among the various components of the NSI is both complex and multifaceted. Yet, the availability of data about articles and patents justifies the use of these indicators as proxies of science and technology (C&T) with the additional possibility of analyzing the pattern of interaction between them, both for the national innovation system and for the health innovation system. The panel data and simultaneous equations models analyze the interactions between C&T. The basic theory about the existence of a mutual sense of determination between them has been confirmed, which means that science moves technology and technology also influences scientific development.From this outline, it was possible to investigate quantitatively mental health by comparing the scientific technological area with the one involving mental health care. Two typologies of countries were established. The first one, similar to that set up for the health sector, identifies those countries that have a systematic production of C&T in mental health. The second, using a new database, regroups those countries with similar characteristics as concerns mental health care. The comparison of the results made it possible to see the continuing presence of the same countries in two extreme groups: on one hand the best countries in the world in terms of C&T in general health are also the best ones in C&T in mental health and have the best infra-structure in mental health care as well; on the other hand, the worst countries in the world in C&T in general health and mental health have the worst infra-structure in mental health care.